Ustilago nigra, especie nueva para la flora argentina y uruguaya - Hirschhoorn, Elisa (1962)
Observation on carácter of spores, chlamydespores and germinationtype of 185 specimens of barley fromm different regions of this country and the Republic of Uruguay, attacked by smut, permit to establish the existence of: 1) Ustilago nigra (a new kind of plague in Argentine an Uruguay), and, 2) individuals with characteristic proper to the hybrids interspecific between U. nigra abd U. bordei, as described by Bever.